Overview of Avian Corona virus, its prevention and control Measures - Abdul Samad; Haseeb Ahmad; Muhammad Hamza; Ayesha Muazzam; Areeb Ahmer; Sania Tariq; Hafeez Ur Rehman Ali Khera; Ujala Mehtab; Muhammad Junaid Shahid; Waseem Akram; Muhammad Zain Kaleem; Shehroz Ahmad; Ahmad Abdullah; Shahryar Ahmad; Fares M Muthanna (CV. Multi Kreasi Media, 2022)
Avian Corona virus is a disease which is effecting bird’s upper respiratory tract. It is caused by Corona virus which belongs to family Corona viridae. This also called Infectious Bronchitis as this infects the bronchioles and can also cause highest mortality ratio. The way of spreading of disease is Aerosol means that disease can transfer from bird to bird through air and it can also spread out through droppings of birds. This study will provide a support to diagnose of disease and also give a proper policy to fight with disease in order to minimize the mortality rate. Avian Corona virus is a viral disease so there is no treatment for it but there are some precautionary measures and vaccination program which will be help to minimize the mortality rate. Due to its spreading mode which is air it has small or short tenure of incubation period means if virus enters in a shed it will effect 100% flock in short time, so we need to stop that virus from entering in the shed so for this reason we need follow the given precautionary measure. Aim of this study is to minimize the economic loss due to Avian Corona virus and to give some extra knowledge to the people related to poultry industry.